Retracing the Spirituality of Tuan Guru M. Zaini Abdul Ghani: Study of Guru Sekumpul Sufism Thinking as Social Piety and Individual Piety - SAM, Siswoyo Aris Munandar (Journal of Islamic History and Manuscript, 2023)
As one of the influential figures of Sufism, Muhammad Zaini Abdul Ghani has many followers and students. He helped form a generation of influential scholars and Sufism figures in the archipelago, so his influence continues today. However, even though his influence is still being felt today, there is also criticism of the thoughts and teachings of Sufism Muhammad Zaini Abdul Ghani. Some people think that the teachings of Sufism need to be more complex and need to meet the requirements of Sufism. However, despite this, the teachings of Sufism Muhammad Zaini Abdul Ghani are still being studied and understood by many people today. This study aims to describe the views of Tuan Guru M. Zaini Abdul Ghani about the scientific treasures of Sufism and to describe the main points of Tuan Guru M. Zaini Abdul Ghani's tasawuf thoughts regarding the concept of Sufism and its significance in everyday life. This research is library research or library research. The approach used is historical and mystical approaches. The results of this study Tuan Guru embodies Nūr Muḥammad in the form of practices and teachings that can be practiced by every group so that the style of this concept is more inclined towards moral tasawuf than philosophy. The transformation that was carried out was visible in every action. In addition, Tuan Guru taught Sufism as an individual fault and a social error by engaging in the economic field.